2020
DOI: 10.1155/2020/7914957
|View full text |Cite
|
Sign up to set email alerts
|

Noncoding RNAs in Vascular Aging

Abstract: Increases in age are accompanied by vascular aging, which can lead to a variety of chronic diseases, including atherosclerosis and hypertension. Noncoding RNAs (ncRNAs) have become a research hotspot in different fields of life sciences in recent years. For example, these molecules have been found to have regulatory roles in many physiological and pathological processes. Many studies have shown that microRNAs (miRNAs) and long ncRNAs (lncRNAs) also play a regulatory role in vascular aging. Endothelial cells (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 126 publications
(124 reference statements)
0
18
0
Order By: Relevance
“…LncRNAs have been demonstrated to possess important functions in various biological processes, such as epigenetic modulation, transcriptional and post-transcriptional regulation ( Feng et al, 2006 ; Wang et al, 2016 ). It has been reported that lncRNAs participate in the regulation of cell senescence ( Azzalin et al, 2007 ; Abdelmohsen et al, 2013 ; Cao et al, 2020 ). MALAT1 and MIAT, known as the best-annotated lncRNAs, exhibit lower expression levels in senescent WI-38 cells.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have been demonstrated to possess important functions in various biological processes, such as epigenetic modulation, transcriptional and post-transcriptional regulation ( Feng et al, 2006 ; Wang et al, 2016 ). It has been reported that lncRNAs participate in the regulation of cell senescence ( Azzalin et al, 2007 ; Abdelmohsen et al, 2013 ; Cao et al, 2020 ). MALAT1 and MIAT, known as the best-annotated lncRNAs, exhibit lower expression levels in senescent WI-38 cells.…”
Section: Discussionmentioning
confidence: 99%
“…in addition, patients with IS are prone to a hypercoagulable state and advanced fibrinolysis. Most patients have coagulation changes in the clinic, which may lead to adverse events such as thrombosis and infarction, which affects the prognosis (50).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we have focused on their role in VSMCs. However, there is also a large body of literature documenting their important roles in regulating endothelial cell function (Wei et al, 2013 ; Cao et al, 2020 ). Thus, an important next step in this field will be to assess whether manipulating miRNA levels in VSMCs selectively is sufficient to induce or prevent arterial stiffening or whether parallel processes in endothelial cells or other cells present in large vessels, such as immune cells or fibroblasts, also play a key role in the pathophysiology of LAS.…”
Section: Summary and Future Directionsmentioning
confidence: 99%